การสืบค้นภูมิปัญญาแพทย์พื้นบ้านอีสานในคัมภีร์ยาใบลาน The Research on the Wisdom of Local Isan Medicine in Khamphi Bai-Lan (Scripture Written on Palm-leaves). - Krisada Sridharmma กฤษฎา ศรีธรรมา (วารสารมหาวิทยาลัยราชภัฏมหาสารคาม, 2015)
การวิจัยเรื่องการสืบค้นภูมิปัญญาแพทย์พื้นบ้านอีสานในคัมภีร์ยาใบลานมีวัตถุประสงค์เพื่อศึกษาความรู้ ในการบำบัดรักษาโรคของแพทย์พื้นบ้านอีสานที่ปรากฏในคัมภีร์ยาใบลานอีสาน จำนวน 2 ผูก คือ คัมภีร์ยาจากหนังสือก้อมใบลานฉบับวัด บ้านโกทา ตำบลพระธาตุ อำเภอนาดูน จังหวัดมหาสารคาม และคัมภีร์ยาฉบับพระชิน ฐิติธัมโม บ้านวังบัว ที่ได้เก็บรักษาไว้แล้วปริวรรตเป็นอักษรไทยปัจจุบันเพื่อศึกษาความรู้ในการบำบัดรักษาโรคของแพทย์พื้นบ้านอีสานเพิ่มเติม ตลอดจนสืบค้นสมุนไพร ที่ปรากฏในคัมภีร์ยาใบลานอีสานในพื้นที่จังหวัดมหาสารคาม ร้อยเอ็ด และกาฬสินธุ์ ผลการวิจัยพบว่าคัมภีร์ยาในใบลานอีสานบันทึกด้วยอักษรไทยน้อยและอักษรธรรมเป็นภาษาอีสานโบราณ กล่าวถึงโรคและการรักษาโรค โดยใช้สมุนไพร ที่ได้จากพืช สัตว์ แร่ธาตุในท้องถิ่น และใช้วิธีการนวดการบริหารร่างกาย ในการรักษาผู้ป่วยทางด้านร่างกาย และจิตใจ แพทย์พื้นบ้านจะรักษาด้วยคาถา พิธีกรรม การใช้ยาสมุนไพรประกอบ เพื่อให้เกิดผลด้านจิตใจส่งผลให้ผู้ป่วยหายเร็วขึ้น แสดงให้เห็นถึงภูมิปัญญาท้องถิ่นของแพทย์พื้นบ้านอีสานในการเก็บยา กรรมวิธีปรุงยา และกรรมวิธีในการรักษาสุขภาพ ด้วยวิถีท้องถิ่น The research on the wisdom of local Isan medicine in Khamphi Bai-Lan aimed to study how to cureillness by local Isan physicians which appeared on two Khamphi Bai Lan texts. They are the sacred books ofmedicine from the short Bai Lan of Ban Kotha temple, Phrathat sub-district, Na Doon district, Mahasarakham and the sacred book of medicine of Phra Chin Thitidharmmo Banwangbua which is kept and changed intomodern Thai consonants in order to study how to cure illness in the local Isan way and to search for herbswhich appeared in Khamphi Bai Lan Isan in the area of MahaSarakham, Roi-Ed and Kalasin. The result of the research revealed that the Isan Khamphi Bai Lan on medicine written in Thai Noiand Dharmma consonants are ancient Isan Ianguage mentioning about diseases and cure by herbs and magicwords. They show the local wisdom of Isan art of medicine in collecting medicine, method of medical making and health care by local way. Isan local physicians cure the patients by using herbs from plants, animals and minerals in the local ; and by massage to cure both mental and physical illness. The local physicians will cure by using magic words, rites and herbs which affects the mental condition of the patients faster.